Small and Medium Enterprises’ Impact on Achieving the Sustainability in Agricultural Sector for Rural Development - Gunasekara, A.N.N.M. (University of Jaffna, 2021)
In the journey towards the sustainable development, the agricultural sector plays a major role in socio economic context. Many successful governments have taken the necessary steps to develop the agricultural sector in the light of policy implications. Sustainable development in the agriculture sector ensure food security, creating employment opportunities, mitigating wastage, alleviating poverty, and improving living standards while achieving higher economic growth. This study scrutinized the challenges and prospects of the agricultural sector in reference to SME. The study aimed to promote SME as an effective tool for empowering agriculture in the rural sector along the journey of sustainable development by examining the current status, challenges, and prospects of SMEs to promote sustainable agriculture for rural development and direct policymakers towards effective and efficient policy implications for Agricultural SME in Nuwara Eliya and generalize it upon the success. Data were collected using convenient sampling method. Qualitative research methods such as in-depth analysis of literature, semi-structured questionnaire interviews, farm observations, focus group discussions, key informant interviews were employed to collect data from 40 respondents. The thematic analysis was performed and found that the small medium enterprises employers and employees commonly expressed the fact that their existing production practices are not at their highest level and that fact hinders the progress towards sustainable development in their production. The main reasons according to them were, fragmentation of land, high cost occurrence for inputs, lack of knowledge, inefficiency in production, distortion of markets, government, and market failure, lack of efficient infrastructure, misappropriation of fertilizer usage, lack of skills, and young energetic workers tend to leave farming and migration to the industrial sector. The empirical evidence of this study confirms that the relevant authorities should address the persisting government failures, market failures asymmetric information, the attraction of public-private investment, the introduction of novel technologies, and business development strategies. The findings further confirmed the urgency of sustainable policy planning and implication, a strong legal system to strengthen the economies of scale, development of infrastructure facilities in terms of logistics, communication, financial aspects, and encouragement of youth towards agricultural activities.
Keywords: agricultural development; policy Implications; small Medium enterprises